The Production Performance Of Malaysia’S Food Processing Industry - Lee, Yong Chin (2024)
The food processing industry (fpi) plays a significant role in malaysia's economy, but it faces ongoing challenges with low productivity and negative production growth, which indicates potential inefficiency concerns, particularly within its five sub-sectors. These issues may be partly attributed to economic shocks like the 2009 financial crisis, which impacted access to financing, supply chain stability, and investment in productivity-enhancing technologies. Hence, the main objectives are to analyze the production performance of malaysia’s fpi. The first objective is to determine the level of efficiency and productivity of the small and medium-sized enterprises (smes) and large-scale enterprises (lses) in malaysia’s fpi. Secondly, it aims to examine the factors affecting productivity and inefficiency. Lastly, it aims to assess the impact of productivity and other macroeconomic factors on the production growth in malaysia’s fpi. To achieve this, the study utilizes total factor productivity (tfp) instead of partial productivity measures like labour or capital productivity, as tfp offers a more comprehensive assessment by encompassing all production inputs and reflecting overall productivity levels.